Integrasi Total Quality Management (Tqm) dan Building Information Modelling (Bim) untuk Meningkatkan Pengelolaan Mutu Proyek Konstruksi - Faradiba Dwi Hernita; Tri Joko Wahyu Adi (Institut Nalanda, 2026)
This study aims to develop an integration model of Total Quality Management (TQM) and Building Information Modeling (BIM) based on Lean Management and Industry 4.0 Technology to support the improvement of construction project quality management in the development of Indonesia’s New Capital City (Ibu Kota Nusantara—IKN). The study was conducted by identifying TQM principles, BIM dimensions, Industry 4.0 technologies, Last Planner System (LPS) elements, and construction project quality aspects, including defect reduction, rework minimization, waste registers, and performance quality. The research employed both qualitative and quantitative descriptive approaches through literature reviews, project observations, integration matrix development, questionnaire distribution to 12 expert respondents, Content Validity Ratio (CVR) analysis, and Focus Group Discussion (FGD). The results indicate that TQM–BIM integration has a positive influence on construction project quality management. The most dominant integrations were found between BIM 4D and Percent Plan Complete (PPC) Evaluation, BIM Workflow and Pull Planning, as well as data-driven decision-making through BIM 5D and constraint management. The resulting integration model supports collaborative planning, real-time data-based project monitoring, and continuous improvement in construction project quality management. Furthermore, the implementation of the model has significant potential to support digital construction in IKN projects, although challenges remain regarding the integration of digital quality systems, human resource readiness, and coordination among project stakeholders.